Microwave radiation associated with positive narrow bipolar events. (January 2023) - Baharin, Shamsul Ammar Shamsul; Ahmad, Mohd Riduan; Sabri, Muhammad Haziq Mohammad; Alammari, Ammar; Al-Kahtani, Ammar Ahmed Nasser; Lu, Gaopeng; Kawasaki, Zen; Cooray, Vernon
Abstract: In this paper, we examined seven isolated positive Narrow Bipolar Events (NBEs), one positive NBE that initiated an IC flash progressed to a single-stroke Cloud-to-Ground (CG) flash, and one positive NBE that initiated an IC flash. Seven NBEs have been accompanied by significant Very-High Frequency (VHF) and microwave radiation pulses. We recorded all NBEs from two measurement stations (ST1 and ST2) separated at 13.3 km apart which consisted of fast antenna (FA) and slow antenna (SA) sensors, a magnetic field (B-field) sensor, a VHF sensor (60 MHz), and a microwave sensor (0.97 GHz). The waveforms were sampled at 2.5 GHz (400 ps). The key finding is that all microwave radiation pulses have been found to precede both the VHF radiation pulses and NBEs with average lead time of 63 ± 39 ns and 122 ± 143 ns, respectively. In comparison to stepped leader pulses or SLPs (conventional breakdown), the average lead time of microwave to VHF for NBEs (fast breakdown) was 88% faster compared to the average lead time of microwave to VHF for SLPs. Moreover, the average lead time of VHF to NBEs was 56% faster when compared to the average lead time of VHF to SLPs. The VHF interferometer map for an isolated NBE (NBE6) showed upward propagation of VHF radiation sources (fast negative breakdown) with initiation altitude, total length of the VHF radiation sources propagation, and estimated velocity were 10.2 ± 0.3 km, 2.9 ± 0.6 km, and 1.8 × 10 8 and 2.8 × 10 8 ms −1, respectively. On the other hand, interferometer map for an NBE that initiated a single-stroke CG (NBE3) showed bidirectional fast streamers propagation with initiation altitude, total length of the VHF radiation sources propagation, and estimated velocity were 14.0 ± 0.4 km, 2.9 ± 0.82 km, and 1.6 × 10 8 and 2.8 × 10 8 ms −1, respectively. Clearly, the microwave and VHF radiation pulses associated with positive NBEs have been emitted by different processes of fast breakdown mechanism. Therefore, it can be suggested that the microwave radiation is emitted by electron avalanches/corona while the VHF radiation is emitted by fast propagating streamers. Highlights: All microwave radiations preceded VHF radiations with average lead time 63 ± 39 ns. All microwave radiations preceded NBEs with average lead time 122 ± 143 ns. Microwave radiation is suggested to be associated with electron avalanches/corona. VHF radiations were associated with fast propagating streamers (fast breakdown). The fast streamers were propagated vertically either in unidirectional or bidirectional manner.